GENE THERAPY IN MUCOPOLYSACCHARIDOSIS TYPE IIIA: CASE REPORTS - Benjamin Lah; Tadej Jalšovec; Ana Drole Torkar; Jana Kodrič; Saba Battelino; Mojca Žerjav Tanšek; Tadej Battelino; Urh Grošelj (The Society for Children with Metabolic Disorders, 2022)
Mucopolysaccharidoses are a group of rare lysosomal storage diseases. The clinical signs develop gradually, the impairment is progressive and multiple organs are affected. With the currently known treatment options, the patient cannot be cured. However, with the arrival of effective gene therapy, together with early diagnosis and treatment, successful treatment is possible. Firstly, we present the case of a boy whose older brother's disease enabled early diagnosis and then access to experimental gene therapy abroad, which until the present appears to have been successful. The second case is a boy, where an early diagnosis was made due to an early clinical suspicion and appropriate laboratory investigations. Consequently, experimental gene therapy abroad became possible. Both cases belong to a group of five Slovene children who underwent successful gene therapies; all of them as a part of study protocols abroad. Gene therapy is now becoming a clinical reality. Early diagnosis is the key to successful gene therapy for mucopolysaccharidosis; in the future probably also with newborn screening programmes.